Potential Measurements on Rubber Surfaces in Electrolyte Solutions - Badri, M.; Crouse, Karen Anne (Universiti Putra Malaysia Press, 1995)
Films of natural and modified rubber were prepared and used as electrode membranes. The potential developed varied with the concentration of ions in solution and is discussed in terms of adsorption of the ions onto the membrane.